ABIN1 is a negative regulator of effector functions in cytotoxic T cells - Janusova, Sarka; Paprckova, Darina; Michalik, Juraj; Uleri, Valeria; Drobek, Ales; Salyova, Eva; Chorfi, Louise; Neuwirth, Ales; Andreyeva, Arina; Prochazka, Jan; Sedlacek, Radislav; Draber, Peter; et al. (EMBO reports, 2024)
T cells are pivotal in the adaptive immune defense, necessitating a delicate balance between robust response against infections and self-tolerance. Their activation involves intricate cross-talk among signaling pathways triggered by the T-cell antigen receptors (TCR) and co-stimulatory or inhibitory receptors. The molecular regulation of these complex signaling networks is still incompletely understood. Here, we identify the adaptor protein ABIN1 as a component of the signaling complexes of GITR and OX40 co-stimulation receptors. T cells lacking ABIN1 are hyper-responsive ex vivo, exhibit enhanced responses to cognate infections, and superior ability to induce experimental autoimmune diabetes in mice. ABIN1 negatively regulates p38 kinase activation and late NF-κB target genes. P38 is at least partially responsible for the upregulation of the key effector proteins IFNG and GZMB in ABIN1-deficient T cells after TCR stimulation. Our findings reveal the intricate role of ABIN1 in T-cell regulation.
Keywords: receptory antigenů T-buněk; Interferon-gamma; Mice, Inbred C57BL; Animals; Lymphocyte Activation; Glucocorticoid-Induced TNFR-Related Protein; Receptors, Antigen, T-Cell; p38; Humans; Mice; myši inbrední C57BL; Antigen Receptor; glukokortikoidy indukovaný protein související s TNRF; Adaptor Proteins, Signal Transducing; p38 Mitogen-Activated Protein Kinases; cytotoxické T-lymfocyty; Receptors, OX40; Co-stimulation; aktivace lymfocytů; T-Lymphocytes, Cytotoxic; T Cells; ABIN1; zvířata; adaptorové proteiny signální transdukční; Diabetes Mellitus, Type 1; myši knockoutované; interferon gama; diabetes mellitus 1. typu; receptory OX40; lidé; Signal Transduction; NF-kappa B; Mice, Knockout; signální transdukce; myši; mitogenem aktivované proteinkinasy p38